Korelasi Dukungan Keluarga dengan Kejadian Self Harm pada Remaja - Andi Bunga Tenri Ayu; Alfunnafi Fahrul Rizzal; Indari Indari (Pusat riset dan Inovasi Nasional, 2026)
Self-harm among adolescents is a mental health problem influenced by various psychosocial factors, including family support. The family serves as the primary support system that can protect adolescents from the effects of stress and maladaptive coping behaviors. This study aimed to analyze the relationship between family support and the incidence of self-harm among adolescents. The study employed an analytic quantitative design with a cross-sectional approach. The research sample consisted of 476 adolescents selected using a cluster random sampling technique. Family support was measured using the Perceived Social Support–Family (PSS-Fa) questionnaire, while the incidence of self-harm was assessed using the Self-harm Inventory (SHI). Data were analyzed using the Spearman Rank test. The results showed that the majority of respondents had high levels of family support (65.8%) and did not engage in self-harm (78.2%). Bivariate analysis indicated a significant relationship between family support and the incidence of self-harm among adolescents (p < 0.001), where adolescents with high family support were more likely to be in the non–self-harm category, while mild and severe self-harm were more commonly found among adolescents with low family support. This study concludes that family support plays an important role as a protective factor against self-harm among adolescents. Strengthening the role of the family should be a key focus in family-based nursing interventions for the prevention of mental health problems in adolescents.